Análise da influência dos parâmetros de qualidade sobre a remuneração dos produtores de leite - (:unkn) unknown (Universidade Federal de Goiás, 2016)
Despite the importance of the dairy industry chain to Brazil, producers still have difficulty to fit the parameters and quality terms of the Normative Instructions 51, 62 and paragraph 07 of the Ministry of Agriculture, Livestock and Food Supply (MAPA). Besides, the national productivity is much lower than the major world producers. Thus, the payment for quality is a strong influencer for the production of milk with quality, and the Somatic Cell Count (SCC) directly linked to mastitis, which is a major production reduction factor. Therefore, this paper has as the main objective to look for evidences that prove if the quality of refrigerated raw milk impacts the remuneration of farmer/dairy industry X, located in the south of the state of Goiás, regarding two specific aspects: the financial impact of paying for quality, based on indicators that show the total count of bacteria (TCB), somatic cell count (SCC), fat and protein according to Normative Instruction No. 07 of the Ministry of Agriculture, Livestock and Food Supply (MAPA) and the impact of CCS on production. This is an applied research, so by the descriptive statistical method and also the results and researches crossing technique regarding the theme analyzed, in order to verify possible evidence of the relation quality versus remuneration 26,8 thousands samples was analyzed, from November 2011 to May 2016. It was found that there is evidence of the influence of quality on the remuneration of the farmers/dairy industry X, regarding the goodwill, it was higher than the negative goodwill in the years 2011-2015, with an average income of R$ 2,087 million/ month, and negative only for CCS in 2016. The results of the payment for quality proved to be able to motivate the producer to produce milk with quality due to financial increase, causing the producer to add value to its raw material. Regarding the impact of CCS on the production, was found a reduction of 9.84% in the total of milk produced in those five years analyzed, with an average reduction in production of 2,663 million liters per month, resulting in a reduction in income by farmers/dairy industry of R$ 2,972 million per month, being significant the impact of CCS on production.
Analysis of the influence of the quality parameters and financial returns of milk producers
Keywords: Parâmetros de qualidade do leite; Remuneração dos produtores de leite; Pagamento por qualidade e produção; Milk quality parameters; Remuneration of farmers/dairy industry; Payment for quality and production; ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS